Environmental Management Based on Islamic Sharia and Customary Law in Aceh - zahratul idami; Israr Hirdayadi; Qudwatin Nisak M Isa; Alfi Rahman (Fiat Justisia: Jurnal Ilmu Hukum, 2022)
This paper discuss how Islamic and customary laws regulate environmental management in Aceh. A qualitative approach was used by implementing a normative juridical method. First, the data from various literature or references and documents were gathered related to the topic. It was then qualitatively analysed using the concept, constitutional and historical approaches, and Islamic environmental management regulations. According to the study's findings, the Islamic Shari'a and Aceh Customary Law cannot be separated, citing the hadith Maja "Adat ngon hukom lagee zat ngon sifeut." All customary law-based environmental management adheres to Islamic law. In the Prophet's hadith, whoever cut the sidr tree will go to hell. Under the customary law of Aceh, it is prohibited to cut trees tualang, kemuning, ketapang, etc in the forest. Except with Keujreun's permission. According to Aceh Customary Law, anyone who keeps livestock must be careful to keep them restrictions in opening land in a specific location, such as a spring source. All humans have the legal status of muhtaram in Islamic Law, not in an honourable sense. Still, their existence must be protected as living beings as well as lifeless beings, and all must be protected by their existence rights.